Composite cosmetic powder with water resistance and skin fitness and preparation method

By coating amino acids, natural vegetable oils and synthetic oils on the surface of the titanium dioxide powder, forming a multi-layer oil coating composition, solving the problem of uneven dispersion and aggregation of titanium dioxide powder in cosmetics, and achieving excellent water resistance of composite cosmetic powders Sex and skin obedience.

CN119488440APending Publication Date: 2025-02-21KOLMAR COSMETICS (WUXI) CO LTD +1

Patent Information

Application Number
CN202411836970.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing titanium dioxide powders are prone to problems such as uneven dispersion and agglomeration due to surface reactivity in cosmetics, and some modification methods may cause the powder to accumulate and affect the skin feeling.

Method used

By using the composite modification method, the surface of the titanium dioxide powder is coated with amino acids, natural vegetable oils and synthetic oils to form a multi-layer oil coating composition, thereby improving the water resistance of the powder and skin compliance.

Benefits of technology

It achieves excellent hydrophobicity, water resistance and skin obedience of composite cosmetic powder, giving cosmetics a good sense of use, makeup effect and makeup holding effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488440A_ABST
    Figure CN119488440A_ABST
Patent Text Reader

Abstract

The invention provides composite cosmetic powder with water resistance and skin fitness and a preparation method thereof.The composite powder comprises titanium dioxide, amino acid, natural vegetable oil and synthetic grease, the preparation method comprises the steps that firstly, titanium dioxide powder is added into deionized water to be prepared into 40% aqueous dispersion, an amino acid solution is added to form reaction liquid, and the reaction liquid is added into the deionized water; adjusting the pH value of the reaction liquid to 7-8 so as to coat the hard amino acid; aging, filtering, washing, drying and crushing the reaction liquid to obtain composite modified titanium dioxide powder; adding the composite modified titanium dioxide powder into a high-speed mixer, and sequentially adding synthetic grease and natural vegetable oil along with the operation of the mixer; the composite cosmetic powder is obtained through drying and smashing, and the powder prepared through the proportion and the method has excellent adhesive force and spreadability, proper covering power, a good soft coke effect, prominent water resistance and water resistance and a good makeup maintaining effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cosmetics, and in particular relates to a composite cosmetic powder with water resistance and skin adherence and a preparation method thereof. Background Art

[0002] Titanium dioxide is a coloring pigment with excellent hiding power and tinting power, as well as good stability and safety. It is often used in the cosmetics field to express or improve the color and gloss of the skin. Unmodified titanium dioxide has significant surface reactivity. In the formula, it may react or aggregate with other ingredients in the formula due to the surface charge adsorption of the particles, covalent or ionic chemical reactivity, resulting in unacceptable phenomena such as uneven dispersion, agglomeration, fine sand texture, floating powder, and precipitation of titanium dioxide powder in the product. In order to overcome these problems, we have long been accustomed to surface treating titanium dioxide powder, uniformly coating the surface of the particles with inorganic and organic substances to make it hydrophilic or hydrophobic, and improve the application performance in the formula. Usually, we use inorganic coating to reduce the exposed reactive groups on the surface of titanium dioxide particles, reduce surface activity and photoactivity, and improve water dispersibility. Organic coating is used to give titanium dioxide particles hydrophobicity, inhibit particle agglomeration, enhance dispersibility and compatibility in oil phase components, and improve the skin-fitting, spreadability, uniformity and overall skin feel of the finished product.

[0003] There are many patents and literatures on the surface modification of titanium dioxide pigments. Common coating methods are inorganic surface modification, organic surface modification and composite modification. Common inorganic modifiers include aluminum hydroxide, silicon oxide, aluminum oxide and zirconium oxide. Common organic surface modifiers can be roughly divided into silicone oils, coupling agents, fatty acids and fatty acid salts, amino acids, surfactants, base oils, etc.

[0004] US Patent No. 6200580B1 discloses a reactive alkyl polysiloxane and methyl hydrogen polysiloxane modified powder material and its use. The powder obtained by the invention has excellent adhesion to the skin, no flocculation, and a particularly smooth touch. It is also very excellent in hydrophobicity and water resistance. However, the final product still has the characteristic of residual active hydrogen, which may lead to the release of hydrogen that is harmful to the final product.

[0005] US Patent No. 5562897A discloses an alkoxysilane-modified titanium dioxide powder material. Alkoxysilane hydrolyzes when heated in the presence of water to produce silanol groups, which condense, crosslink and couple to hydroxyl groups on the surface of the powder substrate to achieve good hydrophobicity. However, the reaction process may cause aggregation of powder particles, affecting the skin feel of the powder.

[0006] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies in the prior art. The present invention provides a composite cosmetic powder having water resistance and skin conformability and a preparation method thereof.

[0008] In order to achieve the above object, the present invention provides the following technical solutions: A composite cosmetic powder with water resistance and skin adherence, the composite powder comprising titanium dioxide, amino acid, natural vegetable oil and synthetic oil.

[0009] Preferably, the amino acid is any one or more of lauroyl lysine, disodium stearoyl glutamate, sodium lauroyl aspartate, sodium lauroyl glutamate, lauroyl lysine, lauroyl sarcosine, and disodium cocoyl glutamate; Preferably, the amino acid is one of lauroyl lysine and disodium stearoyl glutamate.

[0010] Preferably, the natural vegetable oil is one or more of palm oil, shea butter, olive oil, sweet almond oil, camellia oil, jojoba oil, coconut oil, and cactus fruit oil; Preferably, the natural vegetable oil is one or more of cactus fruit oil, shea butter and jojoba oil.

[0011] Preferably, the synthetic oil is one or more of squalane, hydrogenated polyisobutene, caprylic / capric triglyceride, isononyl isononanoate, and silicone oil.

[0012] Preferably, the synthetic oil coating is one or more of squalane and caprylic / capric triglyceride.

[0013] Preferably, the surface of the titanium dioxide is coated with an inorganic coating of aluminum hydroxide.

[0014] Preferably, the amino acid is 1-10 parts by weight; the natural vegetable oil is 1-10 parts by weight; the synthetic oil is 1-10 parts by weight; and the titanium dioxide is 95-100 parts by weight. Preferably, the amino acid is 1-5 parts by weight; the natural vegetable oil is 1-5 parts by weight; the synthetic oil is 1-5 parts by weight; and the titanium dioxide is 95-100 parts by weight.

[0015] Preferably, the active ingredient in the synthetic oil is oil-soluble, and the active ingredient accounts for 0.1%-1% of the weight of the oil.

[0016] A method for preparing a composite cosmetic powder having water resistance and skin conformability comprises the following steps: Step S1, adding titanium dioxide powder to deionized water to prepare a 40% aqueous dispersion, adding an amino acid solution to form a reaction solution, and adjusting the pH of the reaction solution to 7-8 to coat the hard amino acid; Step S2, aging, filtering, washing, drying and crushing the reaction solution to obtain composite modified titanium dioxide powder; Step S3, adding the composite modified titanium dioxide powder into a high-speed mixer, and adding synthetic oil and natural vegetable oil in sequence as the mixer is running; Step S4, obtaining a composite cosmetic powder by drying and crushing.

[0017] Preferably, in step S3, the mixed product is heated to about 80-90° C., maintained for 4 hours, and then cooled to room temperature.

[0018] Preferably, in step S3, firstly, half of the synthetic oil and natural vegetable oil are added in sequence, and after being fully mixed, another half of the synthetic oil and natural vegetable oil are added in sequence.

[0019] Beneficial effects: The composition provided in the present application has excellent hydrophobicity and water resistance, excellent adherence to the skin surface, can give cosmetics excellent use feeling, makeup effect and makeup durability, has excellent adhesion, spreadability and appropriate covering power, good soft focus effect, outstanding waterproofness and water resistance, and good makeup holding effect.

[0020] The powder cosmetic composition of the present invention has no particular restrictions on the form of cosmetics, and can be used in products such as foundation, pressed powder, lipstick, eye shadow, foundation cream, sunscreen, etc. BRIEF DESCRIPTION OF THE DRAWINGS The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them: Figure 1 This is a scanning electron microscope photo of the specific embodiment 1 provided by the present invention; Figure 2 Comparative photos of the stability of the dosage forms of various embodiments provided by the present invention after centrifugation for 5 minutes; Figure 3 This is a comparison chart of the moisturizing effects of various embodiments provided by the present invention; Figure 4 This is a comparison chart of the number of pores in various embodiments provided by the present invention.

[0021] Figure 5 Comparative photos of adhesion of various embodiments provided by the present invention; Figure 6 This is a photo of the composite powder observed by SEM provided by the present invention. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0023] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0024] The main reasons for dull foundation are as follows: 1. The secretions from the skin pores and the oil on the skin surface are one of the main reasons for dull foundation. After the sebum oil secreted by the skin merges with the liquid foundation, the liquid foundation becomes transparent and darker (dissolving makeup); 2. The oil of the foundation itself oxidizes and causes dullness; 3. The color powder is soaked by the skin oil, just like sand becomes dark after being soaked in water, which changes the refraction of light, so that the color becomes darker visually; 4. The film-forming agent is damaged after the makeup is left, resulting in uneven distribution of color powders of different colors, and the powder aggregates to change the original optical effect, so that the color becomes darker visually; 5. The influence of sweat: the foundation becomes darker and more transparent after merging with sweat. We hope to increase the makeup-holding effect of the foundation product by reducing the oil absorption of the powder and improving the water resistance of the powder. Therefore, the present application provides a composite cosmetic powder with water resistance and skin compliance. The composite powder includes titanium dioxide, amino acids, natural plant oils and synthetic oils, among which the plant oil is the essence of the plant, mainly extracted from the seeds and fruits of the plant. They are rich in precious ingredients such as triglycerides, vitamins, trace elements, phytosterols and antioxidants, which bring natural nourishment and care to the skin; in cosmetics, it is not only an emollient, but also can soften the skin, form a closed film, reduce water loss, and keep the skin moisturized. At the same time, the fatty acids in vegetable oils can also stabilize the skin barrier, and have multiple effects such as anti-inflammatory, antibacterial, repair, anti-aging, promoting wound healing and anti-oxidation. Different vegetable oils have different focuses and directions in skin care due to their differences in fatty acid composition and structure, types and contents of accompaniments. In addition to the emollient and repair effects, vegetable oils are also the base oils of cosmetics, which are used to dilute concentrated essential oils, enhance the skin's absorption of essential oils, and reduce the irritation of essential oils to the skin. This makes vegetable oils play a more extensive and important role in cosmetics. In addition, the accompaniments in vegetable oils are also an important part of their skin care effects. These accompaniments include active ingredients such as vitamin E, phytosterols, polyphenol compounds and oryzanol. They each have unique skin care effects, such as anti-oxidation, anti-inflammatory, promoting blood circulation, shielding ultraviolet rays, etc. These accompaniments work together with the fatty acids in the plant oil to provide comprehensive nourishment and protection for the skin. We hope to build a multi-layer natural oil-coated composition so that the powder has skin-fitting, spreadability, water resistance, soft light effect and long-lasting makeup effect. In addition, amino acids are a natural cosmetic raw material with very good affinity with the skin. The material itself has good slippery characteristics. The modified powder is soft and fits the skin, and its spreadability is greatly improved. It also has moisturizing, anti-free radical, anti-allergic and other effects. It is a new generation of cosmetic powder modification material.

[0025] In actual proportioning, the amino acid can be any one or more of lauroyl lysine, disodium stearoyl glutamate, sodium lauroyl aspartate, sodium lauroyl glutamate, lauroyl lysine, lauroyl sarcosine, and disodium cocoyl glutamate; preferably, the amino acid is one of lauroyl lysine and disodium stearoyl glutamate.

[0026] The natural vegetable oil is one or more of palm oil, shea butter, olive oil, sweet almond oil, camellia oil, jojoba oil, coconut oil, and cactus fruit oil; preferably, the natural vegetable oil is one or more of cactus fruit oil, shea butter, and jojoba oil.

[0027] The synthetic oil is one or more of squalane, hydrogenated polyisobutene, caprylic / capric triglyceride, isononyl isononanoate and silicone oil.

[0028] Preferably, the synthetic oil coating is one or more of squalane and caprylic / capric triglyceride.

[0029] Furthermore, the amino acid is 1-10 parts by weight; the natural vegetable oil is 1-10 parts by weight; the synthetic oil is 1-10 parts by weight; and the titanium dioxide is 95-100 parts by weight; preferably, the amino acid is 1-5 parts by weight; the natural vegetable oil is 1-5 parts by weight; the synthetic oil is 1-5 parts by weight; and the titanium dioxide is 95-100 parts by weight.

[0030] In an optional embodiment, the active ingredients in the synthetic oil are oil-soluble, and oil-soluble active ingredients refer to those active substances that can dissolve in oil and exert specific effects in cosmetic formulas. These ingredients usually have a variety of skin care effects, such as anti-oxidation, whitening, moisturizing, anti-inflammatory, etc. The active ingredients can be antioxidants and whitening ingredients, such as VC-IP (ascorbyl tetraisopalmitate): it can have good solubility in oil and excellent skin absorption. Inhibit intracellular tyrosinase activity and melanin production, reduce UV-induced cell / DNA damage (ultraviolet protection), prevent lipid peroxidation and skin aging (anti-oxidation), SOD-like activity (anti-oxidation), collagen synthesis and collagen protection (anti-aging).

[0031] Coenzyme Q10: It can remove excessive free radicals, prevent skin lipid oxidation, prevent damage from free radicals and ultraviolet rays, reduce wrinkles and fine lines, restore skin lipid barrier, promote good function of cell membrane, and improve cell kinetic energy.

[0032] Vitamin E: Anti-free radicals protect the stability of cell membranes. Delaying the aging of the body, using it in pure oil formulas can extend the shelf life of oil products, especially those containing oxidation-sensitive oils.

[0033] Paeonol (peony root extract): can reduce the activity of tyrosinase, prevent cellular lipid peroxidation, reduce skin allergies caused by ultraviolet radiation, and thus reduce the problem of age spots.

[0034] Licorice Extract (Licorice Flavonoids): It is a pure natural whitening and freckle-removing moisturizer. The glycyrrhizic acid salt in the oil-soluble extract can mainly inhibit the activity and diffusion rate of tyrosinase, has a rapid anti-aging whitening and freckle-removing effect, and has a good repair function for the skin.

[0035] Preferably, the active ingredient is 0.1%-1% of the weight of the oil. The titanium dioxide surface is coated with an inorganic coating of aluminum hydroxide. The present invention also provides a method for preparing a composite cosmetic powder having water resistance and skin conformability, which specifically comprises the following steps: Step S1, adding titanium dioxide powder into deionized water to prepare a 40% aqueous dispersion, adding an amino acid solution to form a reaction solution, and adjusting the pH of the reaction solution to 7-8 to coat the hard amino acid.

[0036] Step S2, aging, filtering, washing, drying and crushing the reaction solution to obtain composite modified titanium dioxide powder.

[0037] Step S3, adding the composite modified titanium dioxide powder into a high-speed mixer, and adding synthetic oil and natural vegetable oil in sequence as the mixer is running; further, heating the mixed product to about 80-90° C., maintaining for 4 hours, and then cooling to room temperature.

[0038] The synthetic oil and natural vegetable oil can be added at once or in multiple times. Specifically, first add half of the synthetic oil and natural vegetable oil in sequence, mix them thoroughly, and then add another half of the synthetic oil and natural vegetable oil in sequence. The composite powder is observed by SEM, and the average particle size is about 250nm. Figure 6 .

[0039] Step S4, obtaining a composite cosmetic powder by drying and crushing.

[0040] In an optional embodiment, the titanium dioxide powder is modified by modifying aluminum hydroxide so that the surface of the titanium dioxide is coated with an inorganic aluminum hydroxide coating. The coating process mainly depends on the interaction between the titanium dioxide particles and the aluminum hydroxide, which is usually achieved by electrostatic attraction, heterogeneous nucleation or chemical bonding. Under appropriate conditions, aluminum hydroxide can form a sol and deposit on the surface of the titanium dioxide particles, thereby forming a continuous and uniform coating layer.

[0041] The specific process is: Dispersing titanium dioxide particles in a solution containing an aluminum hydroxide precursor By adjusting the pH value, temperature and other conditions of the solution, the aluminum hydroxide precursor undergoes hydrolysis and polymerization reactions.

[0042] The generated aluminum hydroxide sol is deposited on the surface of titanium dioxide particles and gradually forms a coating layer.

[0043] After subsequent treatments such as washing and drying, coated titanium dioxide powder is obtained.

[0044] This coating layer can improve the photocatalytic performance, dispersibility and weather resistance of titanium dioxide.

[0045] In actual production, it can be prepared specifically by the following examples: Embodiment 1 A titanium dioxide powder composite-modified with 3% aluminum hydroxide and 10% lauroyl lysine was obtained by reasonable proportioning. The powder was added to a high-speed blender, and 2% squalane was sprayed on the powder surface while stirring, and then 3% cactus fruit oil solution was sprayed on the powder surface. The treated powder was transferred to a tray and dried at 90°C for 4 hours, then cooled and crushed at room temperature to obtain a cosmetic composition composite-modified with natural ingredients. The obtained powder showed excellent hydrophobicity, water resistance and skin compliance, with a particle size of 200~250nm, and the particle dispersion state and particle size distribution were uniform, see Figure 1 Scanning electron microscope photograph shown.

[0046] Embodiment 2 Through the above-mentioned modification process of aluminum hydroxide and amino acid, titanium dioxide powder compositely modified with 3% aluminum hydroxide and 5% disodium stearoyl glutamate was obtained. 2% squalane was sprayed on the surface of the powder under stirring, and then 3% cactus fruit oil solution was sprayed on the surface of the powder. The treated powder was transferred to a tray and dried at 90°C for 4 hours, then cooled and crushed at room temperature to obtain a cosmetic composition compositely modified with natural ingredients.

[0047] Based on Example 1 and Example 2, comparison is made through the following comparative examples: Comparative Example 1 The titanium dioxide powder modified by 3% aluminum hydroxide and 10% lauroyl lysine was obtained by the above process. The powder was added to a high-speed mixer, and a mixed solution of 5% squalane and active ingredients was sprayed on the powder surface under stirring. The treated powder was transferred to a tray and dried at 90°C for 4 hours, then cooled and crushed at room temperature to obtain titanium dioxide powder modified by a natural ingredient composition.

[0048] Comparative Example 2 The titanium dioxide powder modified by 3% aluminum hydroxide and 10% lauroyl lysine was obtained by the above process. The powder was added to a high-speed blender, and a 5% cactus fruit oil solution was sprayed on the powder surface under stirring. The treated powder was transferred to a tray and dried at 90°C for 4 hours, then cooled and crushed at room temperature to obtain titanium dioxide powder modified by a natural ingredient composition.

[0049] Comparative Example 3 The titanium dioxide powder compositely modified with 3% aluminum hydroxide and 10% lauroyl lysine is obtained by the above process without natural oil coating.

[0050] Comparative Example 4 Titanium dioxide powder modified with 5% aluminum hydroxide is obtained through the above process.

[0051] For the above comparative examples, multiple aspects such as powder hydrophobicity, powder water resistance, powder oil absorption, dosage form stability, moisturizing effect, soft focus effect, concealer durability, adhesion and adhesion, and feel of use were evaluated as specific methods for each evaluation index.

[0052] Evaluation method of powder hydrophobicity: Transfer 2±0.1g of the sample powder to be tested into a glass beaker containing 100ml of water, stir magnetically for 30min at room temperature and observe the dispersion state of the powder in the layer of water.

[0053] Evaluation method for water resistance of powder: Transfer 2±0.1g of the sample powder to be tested into a glass beaker containing 100ml of water, heat to boiling under magnetic stirring, continue magnetic stirring for 30min and observe the dispersion state of the powder in the layer of water.

[0054] Evaluation method of powder oil absorption: 1) Accurately weigh 5g of powder, accurate to 0.01g; 2) Place the powder on a flat glass plate, add oleic acid with a burette, and add no more than 10 drops of oil each time. After adding, press and grind repeatedly with a spatula to allow the oleic acid to penetrate into the sample; 3) Continue to add oleic acid and press and grind until the oil and sample form a mass; from this point on, grind thoroughly with a spatula after each drop. When a paste with uniform consistency is formed, which is just not cracked or broken and can adhere to the plate, it is the end point; 4) Record the amount of oil consumed, and all operations should be completed within 20-25 minutes. The oil absorption is calculated according to the following formula: Oil absorption = m1 / m0×100, where m0 is the mass of the sample and m1 is the mass of the required oil.

[0055] Evaluation method of dosage form stability: The examples and comparative examples were subjected to viscosity measurement, shaking test, confirmation of stability at different temperatures, and evaluation of formulation stability. The experimental method is as follows. In terms of viscosity, the viscosity of the samples of the above examples and comparative examples on the day of composition manufacture and after storage for 3 months at each temperature (25, 5, 40, 50°C, cycle) was measured under LVT No. 4 * 6rpm conditions, and the viscosity was measured at -18°C, frozen for 24h, and room temperature for 24h for 3 cycles for investigation. In the case of the shaking test, the samples of the above examples and comparative examples were respectively rotated in a centrifuge (Termostable IS-20R Model) at a temperature of 25°C and a speed of 5000rpm for 5 minutes, and the phase separation was confirmed with the naked eye.

[0056] Evaluation method of moisturizing effect: After cleaning the test area with the designated cleanser, leave it in a constant humidity and temperature environment for 10 minutes. According to the product instructions, apply an appropriate amount of sample to the test area and gently apply until it is evenly applied. Use the Corneometer CM 825 from COURAGEKHAZAKA of Germany to test the moisture content of the skin stratum corneum after using the product and evaluate the moisturizing effect of products using different powders.

[0057] Evaluation method of soft focus effect: After cleaning the test area with the designated cleanser, leave it in a constant humidity and temperature environment for 10 minutes. According to the instructions in the product manual, apply an appropriate amount of sample to the test area and gently apply until it is evenly applied. Use Visia 7 to test the amount of facial pores at various time points after product use, and evaluate the soft focus effect of products using different powders.

[0058] Evaluation method of concealer durability: After cleaning the test area with the designated cleanser, leave it in a constant humidity and temperature environment for 10 minutes. According to the product instructions, apply an appropriate amount of sample to the test area and gently apply until it is evenly applied. Use Visia 7 to test the amount of facial spots at various time points after using the product, and evaluate the concealer durability of products using different powders.

[0059] Evaluation methods for adhesion and adhesion: Apply 0.05g of each sample with 50mmX50mm, dry for 30 minutes, and perform adhesion test using 3M610 painting tape.

[0060] Evaluation method of usage feeling: Using the foundation liquid prepared in the examples and comparative examples, 5-10 evaluators aged 20-40 were asked to evaluate the moisturizing feeling, soft focus effect, fit, waterproof effect, ductility, hiding power, makeup lasting effect, dull effect, wrinkle improvement effect, etc. The samples of the above examples and comparative examples were applied to the evaluators' skin, and the sensory organs were divided into 5 levels for evaluation items, with a full score of 5 points, and each level was scored on a 1-point system, with a full score of 5 points. The feeling of use was evaluated by calculating the average of the total score and using the value excluding the deviation.

[0061] The test results of color, hydrophobicity, water resistance and oil absorption are shown in Table 1. The powder prepared in Example 1 has the best hydrophobicity, water resistance and the lowest oil absorption.

[0062] Table 1. Powder indexes of examples and comparative examples The evaluation of formulation stability, moisturizing properties, concealing power, soft focus properties, and adhesion is shown in Table 2.

[0063] Table 2. Formula of cosmetic composition At room temperature, the inorganic powder is dispersed and mixed at high speed, and then placed in the oil phase and thickener, and then placed in a homogenizer (Ultra Mixer, PRIMIX) and pre-dispersed under stirring. After the oil phase is fully stirred, the water phase is slowly added for pre-emulsification. After the water phase is slowly added in its entirety, the main emulsification is performed, and after the completion of the main emulsification, the cosmetic compositions of the examples and comparative examples are degassed to complete.

[0064] The stability of the product at different temperatures was evaluated by viscosity measurement and shaking test, and the experimental method is as follows. In terms of viscosity, the viscosity of the samples of the above-mentioned embodiments and comparative examples on the day of composition manufacture and the viscosity after storage for 3 months at each temperature (25, 5, 40, 50°C, cycle) were measured under LVT No. 4 * 6rpm conditions, and the viscosity was examined by -18°C, freezing for 24h, and room temperature for 24h for 3 cycles. In the case of the shaking test, the samples of the above-mentioned embodiments and comparative examples were respectively rotated in a centrifuge (Termostable IS-20R Model) at a temperature of 25°C and a speed of 5000rpm for 5 minutes, and the phase separation was confirmed with the naked eye. The experimental results are shown in Table 3.

[0065] Table 3. Evaluation of dosage form stability (Centrifugation 5000rpm, 5min, 25℃) The moisture content of the stratum corneum after use is tested, and the moisturizing effect of the formula product is evaluated based on the moisture content. The test method is as follows: 1. After cleaning the test area with the specified cleanser, leave it in a constant humidity and temperature environment for 10 minutes.

[0066] 2. Measure the skin moisture content at various time points after product use.

[0067] 3. According to the product manual, take an appropriate amount of sample and apply it to the test area gently. The test results are shown in Table 4.

[0068] Table 4. Evaluation of formula moisturizing effect By using the comparison to test the moisture content of the skin stratum corneum, the moisture content of the skin stratum corneum of the subjects after using the test samples was significantly improved compared with before use. Figure 3 Through data chart analysis, compared with before use, the moisture content of the stratum corneum of the subjects' skin after using the test samples was significantly improved, indicating that the five test sample foundation liquids all have moisturizing effects, among which Example 1 has the best moisturizing effect.

[0069] The soft focus performance of cosmetics after use is tested, and the concealing and lasting effect of foundation with different powders is determined, as well as the changes in the amount of facial spots and the number of pores. The test machine is Visia 7, and the test temperature is 22 ± 2 ℃, and the relative humidity is 50 ± 5 % in a constant humidity and temperature environment.

[0070] The test method is as follows: 1. After cleaning the test area with the specified cleanser, leave it in a constant humidity and temperature environment for 10 minutes.

[0071] 2. Measure the amount of facial pores at various time points after using the product.

[0072] 3. According to the instructions in the product manual, apply an appropriate amount of sample to the test area and apply it gently until it is evenly applied.

[0073] The results of evaluating the soft focus effect of the formula products by the number of pores are shown in Table 5.

[0074] Table 5. Evaluation of the soft focus effect of the formula To test the concealing durability of cosmetics after use, wash the test area with a designated cleanser and leave it in a constant humidity and temperature environment for 10 minutes. Measure the amount of facial spots at various time points after product use. According to the product instructions, apply an appropriate amount of sample to the test area and gently apply until it is evenly applied. Then evaluate the concealing effect of the formula product based on the amount of spots. The results are shown in Table 6.

[0075] Table 6 Evaluation of formula concealer effect Through data chart analysis, see Figure 4 Compared with before using the product, after using the test samples, the number of pores and spots on the cheeks of the test subjects were significantly reduced, and the pores and spots on the cheeks were still significantly covered and lasted 8 hours after using the test samples, indicating that the five test sample foundation liquids have (8h) concealer lasting effect, among which Example 1 has the best effect.

[0076] The adhesion of cosmetics after use was tested, and the adhesion of the formula products was evaluated based on the powder adhesion in the pictures. The results are shown in Figure 5 , 0.05g of each sample was applied with 50mmX50mm, dried for 30 minutes, and the adhesion test was performed using 3M610 coating tape. The photos on the drawing are photos before and after the adhesion test (upper and lower), and Example 1 has the best adhesion performance.

[0077] A questionnaire survey was conducted on the feeling after using cosmetics. Specifically, the test area was cleaned with a designated cleanser and then left to stand for 30 minutes in a constant humidity and temperature environment. The corresponding questionnaire was filled out 30 minutes, 8 hours, 10 hours, and 12 hours after using the product on the test area (whole face). The specific questionnaire results are shown in Tables 7 and 8.

[0078] Table 7 Evaluation of the product after 30 minutes of use Table 8 Evaluation of the product after 12 hours of use Through data chart analysis, the use effect of each dimension is best when the sample of Example 1 is revisited 12 hours after use.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.

Claims

1. A composite cosmetic powder having water resistance and skin conformability, characterized in that: The composite powder comprises titanium dioxide, amino acid, natural vegetable oil and synthetic oil.

2. The composite cosmetic powder with water resistance and skin conformability according to claim 1, characterized in that: The amino acid is any one or more of lauroyl lysine, disodium stearoyl glutamate, sodium lauroyl aspartate, sodium lauroyl glutamate, lauroyl lysine, lauroyl sarcosine, and disodium cocoyl glutamate; Preferably, the amino acid is one of lauroyl lysine and disodium stearoyl glutamate.

3. The composite cosmetic powder with water resistance and skin conformability according to claim 1, characterized in that: The natural vegetable oil is one or more of palm oil, shea butter, olive oil, sweet almond oil, camellia oil, jojoba oil, coconut oil and cactus fruit oil; Preferably, the natural vegetable oil is one or more of cactus fruit oil, shea butter and jojoba oil.

4. The composite cosmetic powder with water resistance and skin conformability according to claim 1, characterized in that: The synthetic oil is one or more of squalane, hydrogenated polyisobutene, caprylic / capric triglyceride, isononyl isononanoate, and silicone oil; Preferably, the synthetic oil coating is one or more of squalane and caprylic / capric triglyceride.

5. The composite cosmetic powder with water resistance and skin conformability according to claim 1, characterized in that: The surface of the titanium dioxide is coated with an inorganic aluminum hydroxide coating.

6. The composite cosmetic powder with water resistance and skin conformability according to claim 1, characterized in that: The amino acid is 1-10 parts by weight; the natural vegetable oil is 1-10 parts by weight; the synthetic oil is 1-10 parts by weight; the titanium dioxide is 95-100 parts by weight; Preferably, the amino acid is 1-5 parts by weight; the natural vegetable oil is 1-5 parts by weight; the synthetic oil is 1-5 parts by weight; and the titanium dioxide is 95-100 parts by weight.

7. The composite cosmetic powder with water resistance and skin conformability according to claim 1, characterized in that: The active ingredients in the synthetic oil are oil-soluble, and the active ingredients account for 0.1%-1% of the weight of the oil.

8. A method for preparing a composite cosmetic powder having water resistance and skin conformability, characterized in that: The following steps are involved: Step S1, adding titanium dioxide powder to deionized water to prepare a 40% aqueous dispersion, adding an amino acid solution to form a reaction solution, and adjusting the pH of the reaction solution to 7-8 to coat the hard amino acid; Step S2, aging, filtering, washing, drying and crushing the reaction solution to obtain composite modified titanium dioxide powder; Step S3, adding the composite modified titanium dioxide powder into a high-speed mixer, and adding synthetic oil and natural vegetable oil in sequence as the mixer is running; Step S4, obtaining a composite cosmetic powder by drying and crushing.

9. The method for preparing the composite cosmetic powder with water resistance and skin conformability according to claim 8, characterized in that: In step S3, the mixed product is heated to about 80-90°C, maintained for 4 hours, and then cooled to room temperature.

10. The method for preparing a composite cosmetic powder having water resistance and skin conformability according to claim 8, characterized in that: In step S3, firstly, add one half of the synthetic oil and natural vegetable oil in sequence, mix them thoroughly, and then add another half of the synthetic oil and natural vegetable oil in sequence.

Citation Information

Patent Citations

  • Method of protecting the skin

    US5562897A

  • Powdered base material treated with organic silicon compounds and their method for producing

    US6200580B1

  • Oily powder paste with thixotropy and preparation method of oily powder paste

    CN108635241A

  • Preparation method and application of vegetable oil modified titanium dioxide / Maya blue-like composite pigment

    CN113416434A

  • Oil-soluble substance treated powder as well as preparation method and application thereof

    CN115068375A

Cited By

  • Acrylic spray paint with high weather resistance and preparation method thereof

    CN120329799A

  • Cosmetic composition and preparation method thereof

    CN120514630A